2008
DOI: 10.2144/000112905
|View full text |Cite
|
Sign up to set email alerts
|

An Inexpensive and Simple Method for Thermally Stable Immobilization of DNA on an Unmodified Glass Surface: UV Linking of Poly(T)10-poly(C)10–Tagged DNA Probes

Abstract: Microarrays printed on glass slides are often constructed by covalently linking modified oligonucleotide probes to a derivatized surface at considerable expense. In this article, we demonstrate that 14-base oligonucleotides with a poly(T)10 - poly(C)10 tail (TC tag), but otherwise unmodified, can be linked by UV light irradiation onto a plain, unmodified glass surface. Probes immobilized onto unmodified glass microscope slides performed similarly to probes bound to commercial amino-silane-coated slides and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
0
33
1
Order By: Relevance
“…Work reported by the Wolff group has demonstrated an approach to the covalent immobilization of specific primers tagged at the 5' termini with a homopolymer sequence polyT 10 -polyC 10 (TC tag) on unmodified glass slides using simple UV cross-linking [17][18][19]. This resulted in a more stable covalent attachment to the glass surface which sometimes can be an issue in solid-phase amplification [18,20].…”
Section: Approaches For Solid-phase Dna Amplification Microarray Dna mentioning
confidence: 99%
See 2 more Smart Citations
“…Work reported by the Wolff group has demonstrated an approach to the covalent immobilization of specific primers tagged at the 5' termini with a homopolymer sequence polyT 10 -polyC 10 (TC tag) on unmodified glass slides using simple UV cross-linking [17][18][19]. This resulted in a more stable covalent attachment to the glass surface which sometimes can be an issue in solid-phase amplification [18,20].…”
Section: Approaches For Solid-phase Dna Amplification Microarray Dna mentioning
confidence: 99%
“…This resulted in a more stable covalent attachment to the glass surface which sometimes can be an issue in solid-phase amplification [18,20].…”
Section: Approaches For Solid-phase Dna Amplification Microarray Dna mentioning
confidence: 99%
See 1 more Smart Citation
“…UV light exposure is frequently use for sterilization of surfaces and it has also been employed satisfactorily for photo-immobilization [17]. UV light can also promote chemical changes of the exposed materials.…”
Section: Introductionmentioning
confidence: 99%
“…UV exposure has also been used to directly attach oligonucleotides to surfaces including unmodified PMMA. Dufva et al and Gunadson et al have demonstrated the use of poly(T)10-poly(C)10-tagged DNA probes to unmodified and agarose-coated glass surfaces as well as PMMA (Dufva et al 2006;Gudnason et al 2008) and Kimura used oligonucleodtides incorporating a 5'-end poly(dT) tail and and an undisclosed spacer group (Kimura 2006) for attachment to unmodified PMMA.…”
Section: Introductionmentioning
confidence: 99%